2‐Propargyl Alcohols in Organic Synthesis. Issue 14 (5th June 2019) - Qian, Hongwei; Huang, Dayun; Bi, Yicheng; Yan, Guobing
Abstract: 2‐Propargyl alcohols are widely used in organic reactions. Their great success is rooted in the presence of multiple functional groups. This review will focus on six types of mechanisms: (i) 2‐propargyl alcohols as carbocation precursors, (ii) alkynes as electrophiles, (iii) alcohols as nucleophiles, (iv) fracture via ketones or elimination into alkene intermediates, (v) oxidation into alkynyl‐ ortho ‐quinone methides or carbonyl intermediates, and (vi) ring expansions. Reactions involving alkanes, alkenes, alkynes, arenes, alcohols, amines, amides, ketones, CO2, hydrazine, iodobenzene, azides, carbenes, arylboronic acids, etc. will be discussed. We hope that this review will help to promote future research in this area. Abstract :